SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Transportation noise and self-rated health: Evidence from the German national cohort (NAKO) - S. Claire Slesinski; Gabriele Bolte; Sida Zhuang; Tobia Lakes; Eva Rehfuess; Jeroen Staab; Fabian Bamberg; Hansjörg Baurecht; Heiko Becher; Hermann Brenner; Nadine Glaser; Karin Halina Greiser; et al. (Environmental Research, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Ecosystem-wide PFAS characterization and environmental behavior at a heavily contaminated desert oasis in the southwestern U.S. - Jean-Luc E. Cartron; Chauncey R. Gadek; Jonathan L. Dunnum; Christopher C. Witt; Mariel L. Campbell; Samuel J. Romero; Andrew B. Johnson; Julie Kutz; Christopher Wolf; Sarah J. Choyke; Joseph A. Cook (Environmental Research, 2025)

Informatics for toxicokinetics - Gilberto Padilla Mercado; Christopher Cook; Norman Adkins; Lucas Albrecht; Grace Cary; Brenda Edwards; Derik E. Haggard; Nancy M. Hanley; Michael F. Hughes; Anna Jarnagin; Tirumala D. Kodavanti; Evgenia Korol-Bexell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Trade protection via tariff rate quota administration - K. Aleks Schaefer; Christopher A. Wolf (Food Policy, 2025)

Mass spectrometry-based analysis of eccrine sweat supports predictive, preventive and personalised medicine in a cohort of breast cancer patients in Austria - Michael Bolliger; Daniel Wasinger; Julia Brunmair; Gerhard Hagn; Michael Wolf; Karin Preindl; Birgit Reiter; Andrea Bileck; Christopher Gerner; Florian Fitzal; Samuel M. Meier-Menches (EPMA Journal, 2025)
Objective Metabolomics measurements of eccrine sweat may provide novel and relevant biomedical information to support predictive, preventive and personalised medicine (3PM). However, only limited data is available regarding metabolic alterations accompanying chemotherapy of breast cancer patients related to residual cancer burden (RCB) or therapy response. Here, we have applied Metabo-Tip, a non-invasive metabolomics assay based on the analysis of eccrine sweat from the fingertips, to investigate the feasibility of such an approach, especially with respect to drug monitoring, assessing lifestyle parameters and stratification of breast cancer patients. Methods Eccrine sweat samples were collected from breast cancer patients ( n = 9) during the first cycle of neoadjuvant chemotherapy at four time points in this proof-of-concept study at a Tertiary University Hospital. Metabolites in eccrine sweat were analysed using mass spectrometry. Blood plasma samples from the same timepoints were also collected and analysed using a validated targeted metabolomics kit, in addition to proteomics and fatty acids/oxylipin analysis. Results A total of 247 exogenous small molecules and endogenous metabolites were identified in eccrine sweat of the breast cancer patients. Cyclophosphamide and ondansetron were successfully detected and monitored in eccrine sweat of individual patients and accurately reflected the administration schedule. The non-essential amino acids asparagine, serine and proline, as well as ornithine were significantly regulated in eccrine sweat and blood plasma over the therapy cycle. However, their distinct time-dependent profiles indicated compartment-specific distributions. Indeed, the metabolite composition of eccrine sweat seems to largely resemble the composition of the interstitial fluid. Plasma proteins and fatty acids/oxylipins were not affected by the first treatment cycle. Individual smoking habit was revealed by the simultaneous detection of nicotine and its primary metabolite cotinine in eccrine sweat. Stratification according to RCB revealed pronounced differences in the metabolic composition of eccrine sweat in these patients at baseline, e.g., essential amino acids, possibly due to the systemic contribution of breast cancer and its impact on metabolic turnover. Conclusion Mass spectrometry-based analysis of metabolites from eccrine sweat of breast cancer patients successfully qualified lifestyle parameters for risk assessment and allowed us to monitor drug treatment and systemic response to therapy. Moreover, eccrine sweat revealed a potentially predictive metabolic pattern stratifying patients by the extent of the metabolic activity of breast cancer tissue at baseline. Eccrine sweat is derived from the otherwise hardly accessible interstitial fluid and, thus, opens up a new dimension for biomonitoring of breast cancer in secondary and tertiary care. The simple sample collection without the need for trained personnel could also enable decentralised long-term biomonitoring to assess stable disease or disease progression. Eccrine sweat analysis may indeed significantly advance 3PM for the benefit of breast cancer patients.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Trophic cascades and climate change - William J. Ripple; Danielle N. Whalen; Christopher Wolf; Yuanchun Cao; Jessica Schulte; Sarah Swann; Samuel T. Woodrich; Thomas Newsome; Rhys Cairncross; Aaron J. Wirsing (Food Webs, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Valuing water: A global survey of the values that underpin water decisions - Christopher Schulz; Lukas J. Wolf; Julia Martin-Ortega; Klaus Glenk; Maarten Gischler (Environmental Science & Policy, 2024)

Characterization of novel mouse models to study the role of necroptosis in aging and age-related diseases - Ramasamy Selvarani; Hoang Van Michelle Nguyen; Nidheesh Thadathil; Roman F. Wolf; Willard M. Freeman; Christopher D. Wiley; Sathyaseelan S. Deepa; Arlan Richardson (GeroScience, 2023)
To study the impact of necroptosis-induced chronic inflammation on age-related diseases and aging, two knockin mouse models ( Ripk3 -KI and Mlkl -KI) were generated that overexpress two genes involved in necroptosis ( Ripk3 or Mlkl ) when crossed to Cre transgenic mice. Crossing Ripk3 -KI or Mlkl -KI mice to albumin-Cre transgenic mice produced hepatocyte specific hRipk3 -KI or hMlkl -KI mice, which express the two transgenes only in the liver. Ripk3 and Mlkl proteins were overexpressed 10- and fourfold, respectively, in the livers of the hRipk3 -KI or hMlkl -KI mice. Treating young (2-month) hRipk3 -KI or hMlkl -KI mice with carbon tetrachloride (CCl 4 ), a chemical inducer of oxidative stress, resulted in increased necroptosis (Mlkl-oligomers) and inflammation in the liver compared to control mice receiving CCl 4 . Mlkl-oligomerization also was significantly increased in old (18-month) hRipk3 -KI and hMlkl -KI mice compared to old control (Cre negative, Ripk3 -KI and Mlkl -KI) mice. The increase in necroptosis was associated with an increase in inflammation, e.g., inflammatory cytokines (TNFα, IL-6) and macrophage markers (F4/80, CD68). Importantly, steatosis (triglycerides) and fibrosis (e.g., picrosirius red staining, hydroxyproline levels, and transcripts for TGFβ, Col1α1, and Col3α1) that increase with age were significantly higher in the livers of the old hRipk3 -KI or hMlkl -KI mice compared to old control mice. In addition, markers of cellular senescence were significantly increased in the livers of the old hRipk3 -KI and hMlkl -KI mice. Thus, the first mouse models have been developed that allow researchers to study the impact of inducing necroptosis in specific cells/tissues on chronic inflammation in aging and age-related diseases.

Demystifying the agronomic and environmental N performance of grain legumes across contrasting soil textures of central Germany - Ferdinando Binacchi; Wiebke Niether; Christopher Brock; Lucas Knebl; Andreas Brændholt; Benjamin Wolf; Andreas Gattinger (Agriculture, Ecosystems & Environment, 2023)

The ultrastructure of spermatozoa of two species of Aegla (A. parana and A. quilombola) (Crustacea, Decapoda) endemic to Brazil - Milena R. Wolf; Christopher C. Tudge; Sérgio L.S. Bueno; Fernando J. Zara; Antonio L. Castilho (Arthropod Structure & Development, 2023)

Transfer learning in a biomaterial fibrosis model identifies in vivo senescence heterogeneity and contributions to vascularization and matrix production across species and diverse pathologies - Christopher Cherry; James I. Andorko; Kavita Krishnan; Joscelyn C. Mejías; Helen Hieu Nguyen; Katlin B. Stivers; Elise F. Gray-Gaillard; Anna Ruta; Jin Han; Naomi Hamada; Masakazu Hamada; Ines Sturmlechner; et al. (GeroScience, 2023)

“Spider Monkey Cotton”: Bridging Waiwai and Scientific Ontologies to Characterize Spider Monkey (Ateles paniscus) Filariasis in the Konashen Community Owned Conservation Area, Guyana - Christopher A. Shaffer; Marissa S. Milstein; Laramie L. Lindsey; Tiffany M. Wolf; Philip Suse; Elisha Marawanaru; Evan J. Kipp; Tyler Garwood; Dominic A. Travis; Karen A. Terio; Peter A. Larsen (International Journal of Primatology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Human population, social justice, and climate policy - Christopher Wolf; William J. Ripple; Eileen Crist (Sustainability Science, 2021)

A Decade of Incorporating Social Sciences in the Integrated Marine Biosphere Research Project (IMBeR): Much Done, Much to Do? - Ingrid van Putten; Rachel Kelly; Rachel D. Cavanagh; Eugene J. Murphy; Annette Breckwoldt; Stephanie Brodie; Christopher Cvitanovic; Mark Dickey-Collas; Lisa Maddison; Jess Melbourne-Thomas; Haritz Arrizabalaga; Kumiko Azetsu-Scott; et al. (Frontiers in Marine Science, 2021)
Successful management and mitigation of marine challenges depends on cooperation and knowledge sharing which often occurs across culturally diverse geographic regions. Global ocean science collaboration is therefore essential for developing global solutions. Building effective global research networks that can enable collaboration also need to ensure inter- and transdisciplinary research approaches to tackle complex marine socio-ecological challenges. To understand the contribution of interdisciplinary global research networks to solving these complex challenges, we use the Integrated Marine Biosphere Research (IMBeR) project as a case study. We investigated the diversity and characteristics of 1,827 scientists from 11 global regions who were attendees at different IMBeR global science engagement opportunities since 2009. We also determined the role of social science engagement in natural science based regional programmes (using key informants) and identified the potential for enhanced collaboration in the future. Event attendees were predominantly from western Europe, North America, and East Asia. But overall, in the global network, there was growing participation by females, students and early career researchers, and social scientists, thus assisting in moving toward interdisciplinarity in IMBeR research. The mainly natural science oriented regional programmes showed mixed success in engaging and collaborating with social scientists. This was mostly attributed to the largely natural science (i.e., biological, physical) goals and agendas of the programmes, and the lack of institutional support and push to initiate connections with social science. Recognising that social science research may not be relevant to all the aims and activities of all regional programmes, all researchers however, recognised the (potential) benefits of interdisciplinarity, which included broadening scientists’ understanding and perspectives, developing connections and interlinkages, and making science more useful. Pathways to achieve progress in regional programmes fell into four groups: specific funding, events to come together, within-programme-reflections, and social science champions. Future research programmes should have a strategic plan to be truly interdisciplinary, engaging natural and social sciences, as well as aiding early career professionals to actively engage in such programmes.

Climate shifts vs. edaphic humidity and the difficulty of palaeoreconstructions – a malacological study on stable isotopes in Quaternary dune sequences of Fuerteventura - Christiane Richter; Christopher‐Bastian Roettig; Daniel Wolf; Andreas Gärtner; Thomas Kolb; Dominik Faust (Journal of Quaternary Science, 2021)
Dune palaeosurface sequences on the Eastern Canary Islands were investigated for stable isotope records in gastropod shells of the genus Theba . Due to the ecology of the taxon and the special oceanic insularity of the study site, we assume that δ 18 O shell signals in our case mainly reflect shifts in δ 18 O signals of sea surface water. We found that a rapid decrease in δ 18 O shell signals is associated with significant changes in gastropod associations. We suggest that these faunal changes were caused by strong (hot) winds at the end of glacial phases, that were described previously by Moreno et al . In addition, we assume that rapid declines in δ 18 O shell signals due to marine transgressions were followed by geomorphologically stable phases, dominated by dust enrichment. Such palaeosurfaces correlate with maxima of gastropod biodiversity and with more negative δ 13 C shell signals indicating a higher proportion of C3 plants. Based on our results, we also assume that these silty palaeosurfaces were associated with increased soil moisture conditions due to a higher water storage capacity of the finer substrate, independent of climatic moisture conditions.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Global reforestation and biodiversity conservation - Krista M.S. Kemppinen; Pamela M. Collins; David G. Hole; Christopher Wolf; William J. Ripple; Leah R. Gerber (Conservation Biology, 2020)
The loss of forest is a leading cause of species extinction, and reforestation is 1 of 2 established interventions for reversing this loss. However, the role of reforestation for biodiversity conservation remains debated, and lacking is an assessment of the potential contribution that reforestation could make to biodiversity conservation globally. We conducted a spatial analysis of overlap between 1,550 forest‐obligate threatened species’ ranges and land that could be reforested after accounting for socioeconomic and ecological constraints. Reforestation on at least 43% (∼369 million ha) of reforestable area was predicted to potentially benefit threatened vertebrates. This is approximately 15% of the total area where threatened vertebrates occur. The greatest opportunities for conserving threatened vertebrate species are in the tropics, particularly Brazil and Indonesia. Although reforestation is not a substitute for forest conservation, and most of the area containing threatened vertebrates remains forested, our results highlight the need for global conservation strategies to recognize the potentially significant contribution that reforestation could make to biodiversity conservation. If implemented, reforestation of ∼369 million ha would also contribute substantially to climate‐change mitigation, offering a way to achieve multiple sustainability commitments at once. Countries must now work to overcome key barriers (e.g., unclear revenue streams, high transaction costs) to investment in reforestation.

Rock magnetics of carbonate systems–investigating palaeodune archives on Fuerteventura (Canary Islands) - Florian Schneider; Christopher‐Bastian Roettig; Daniel Wolf; Philipp Baumgart; Ulrich Hambach; Dominik Faust (Journal of Quaternary Science, 2020)
The mineral magnetic properties of Pleistocene aeolian dune sands from the island of Fuerteventura (Canary Islands, Spain) were studied in order to reconstruct the palaeoenvironmental evolution of Pleistocene climates during their formation. The palaeodunes on Fuerteventura mainly consist of carbonate sands admixed with dust and material of volcanic origin. Due to the low magnetic background caused by the diamagnetic character of carbonate sands, these archives offer a lot of potential for environmental magnetic studies to detect the imprint of dust, volcanic material and paedogenesis. Four sections of alternating palaeosurface–aeolianite sequences in palaeodune fields have been analysed by means of extensive rock magnetic measurements. These Quaternary archives consist of deposits originating from different sources. I. material blown from the shallow shelf, II. material of volcanic origin, and III. long‐range transported dust. The rock magnetic findings enable a more detailed interpretation of the palaeosurfaces within the sequences. We are able to differentiate semiquantitatively between the different source materials on one hand and to distinguish on the other hand those from soil‐forming processes. Soil formation is only weakly developed in the dust imprints in the palaeosol aeolianite sequences, linked to sparse vegetation cover during the Pleistocene on Fuerteventura.

Constraints on vertebrate range size predict extinction risk - Thomas M. Newsome; Christopher Wolf; Dale G. Nimmo; R. Keller Kopf; Euan G. Ritchie; Felisa A. Smith; William J. Ripple (Global Ecology and Biogeography, 2020)
Aim The only factor in the fossil record that consistently buffers against extinction risk is large geographical range. We ask whether extant vertebrate species with the smallest geographical range for their body size have a higher extinction risk, and thus whether the lower bound of the modern range–body size relationship could serve as an effective conservation prioritization tool. Location Global in scope. Time period Modern. Major taxa studied Six classes of vertebrates. Methods We compiled a database of geographical range, body size and extinction risk for six vertebrate classes ( n = 26,076). We characterized the shape of the relationship between geographical range and body size for each class, using 90% and 10% quantile regression to describe the upper and lower bounds, respectively. We then evaluated the degree of extinction vulnerability of species at the lower bound of the regression using generalized linear mixed models. All analyses accounted for phylogenetic dependence between related species. Results The relationships between species ranges and body sizes were generally positive at both the upper and the lower bounds, and segmented (nonlinear) relationships were common. Despite this variability, species near the lower boundary of the relationship were more often in higher extinction risk categories, and this remained true when the role of range size in the International Union for Conservation of Nature Red Listing criteria was accounted for. Main conclusions Variability in the upper and lower bounds of the range–body size relationship suggests that some classes of vertebrates exhibit combinations of ranges and body sizes that might not reflect historical patterns. Nonetheless, the range–body size relationship remains a reliable and useful predictor of extinction risk, more so than range size does alone. The range–body size relationship could therefore be used to track the trajectories of species towards or away from an extinction threshold and allow the tracking of how different human activities alter the range–body size relationship.

Eating plants and planting forests for the climate - Christopher Wolf; William J. Ripple; Matthew G. Betts; Taal Levi; Carlos A. Peres (Global Change Biology, 2019)

Biomechanical and neurocognitive performance outcomes of walking with transtibial limb loss while challenged by a concurrent task - Alison L. Pruziner; Emma P. Shaw; Jeremy C. Rietschel; Brad D. Hendershot; Matthew W. Miller; Erik J. Wolf; Bradley D. Hatfield; Christopher L. Dearth; Rodolphe J. Gentili (Experimental Brain Research, 2019)

Integrating Ethnography and Hunting Sustainability Modeling for Primate Conservation in an Indigenous Reserve in Guyana - Christopher A. Shaffer; Marissa S. Milstein; Phillip Suse; Elisha Marawanaru; Charakura Yukuma; Tiffany M. Wolf; Dominic A. Travis (International Journal of Primatology, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Serum Response Factor (SRF) Ablation Interferes with Acute Stress-Associated Immediate and Long-Term Coping Mechanisms - Annemarie Zimprich; Gabi Mroz; Christopher Meyer zu Reckendorf; Sofia Anastasiadou; Philip Förstner; Lillian Garrett; Sabine M. Hölter; Lore Becker; Jan Rozman; Cornelia Prehn; Birgit Rathkolb; Kristin Moreth; et al. (Molecular Neurobiology, 2017)

Bayesian characterization of uncertainty in species interaction strengths - Christopher Wolf; Mark Novak; Alix I. Gitelman (Oecologia, 2017)

Quantifying predator dependence in the functional response of generalist predators - Mark Novak; Christopher Wolf; Kyle E. Coblentz; Isaac D. Shepard (Ecology Letters, 2017)
A long‐standing debate concerns how functional responses are best described. Theory suggests that ratio dependence is consistent with many food web patterns left unexplained by the simplest prey‐dependent models. However, for logistical reasons, ratio dependence and predator dependence more generally have seen infrequent empirical evaluation and then only so in specialist predators, which are rare in nature. Here we develop an approach to simultaneously estimate the prey‐specific attack rates and predator‐specific interference (facilitation) rates of predators interacting with arbitrary numbers of prey and predator species in the field. We apply the approach to surveys and experiments involving two intertidal whelks and their full suite of potential prey. Our study provides strong evidence for predator dependence that is poorly described by the ratio dependent model over manipulated and natural ranges of species abundances. It also indicates how, for generalist predators, even the qualitative nature of predator dependence can be prey‐specific.

ADRA2B genotype differentially modulates stress-induced neural activity in the amygdala and hippocampus during emotional memory retrieval - Shijia Li; Riklef Weerda; Christopher Milde; Oliver T. Wolf; Christiane M. Thiel (Psychopharmacology, 2015)

Effects of acute psychosocial stress on neural activity to emotional and neutral faces in a face recognition memory paradigm - Shijia Li; Riklef Weerda; Christopher Milde; Oliver T. Wolf; Christiane M. Thiel (Brain Imaging and Behavior, 2014)

FN14 expression correlates with MET in NSCLC and promotes MET-driven cell invasion - Timothy G. Whitsett; Shannon P. Fortin Ensign; Harshil D. Dhruv; Landon J. Inge; Paul Kurywchak; Kerri K. Wolf; Janine LoBello; Christopher B. Kingsley; Jeffrey W. Allen; Glen J. Weiss; Nhan L. Tran (Clinical & Experimental Metastasis, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Hydrodynamic perception in true seals (Phocidae) and eared seals (Otariidae) - Wolf Hanke; Sven Wieskotten; Christopher Marshall; Guido Dehnhardt (Journal of Comparative Physiology A, 2013)

A plant's perspective of extremes: terrestrial plant responses to changing climatic variability - Christopher P.O. Reyer; Sebastian Leuzinger; Anja Rammig; Annett Wolf; Ruud P. Bartholomeus; Antonello Bonfante; Francesca de Lorenzi; Marie Dury; Philipp Gloning; Renée Abou Jaoudé; Tamir Klein; Thomas M. Kuster; et al. (Global Change Biology, 2013)
We review observational, experimental, and model results on how plants respond to extreme climatic conditions induced by changing climatic variability. Distinguishing between impacts of changing mean climatic conditions and changing climatic variability on terrestrial ecosystems is generally underrated in current studies. The goals of our review are thus (1) to identify plant processes that are vulnerable to changes in the variability of climatic variables rather than to changes in their mean, and (2) to depict/evaluate available study designs to quantify responses of plants to changing climatic variability. We find that phenology is largely affected by changing mean climate but also that impacts of climatic variability are much less studied, although potentially damaging. We note that plant water relations seem to be very vulnerable to extremes driven by changes in temperature and precipitation and that heatwaves and flooding have stronger impacts on physiological processes than changing mean climate. Moreover, interacting phenological and physiological processes are likely to further complicate plant responses to changing climatic variability. Phenological and physiological processes and their interactions culminate in even more sophisticated responses to changing mean climate and climatic variability at the species and community level. Generally, observational studies are well suited to study plant responses to changing mean climate, but less suitable to gain a mechanistic understanding of plant responses to climatic variability. Experiments seem best suited to simulate extreme events. In models, temporal resolution and model structure are crucial to capture plant responses to changing climatic variability. We highlight that a combination of experimental, observational, and/or modeling studies have the potential to overcome important caveats of the respective individual approaches.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Status and future of the forest health indicators program of the USA - Christopher William Woodall; Michael C. Amacher; William A. Bechtold; John W. Coulston; Sarah Jovan; Charles H. Perry; KaDonna C. Randolph; Beth K. Schulz; Gretchen C. Smith; Borys Tkacz; Susan Will-Wolf (Environmental Monitoring and Assessment, 2011)

Reply to comment on “A framework for understanding the hydroecology of impacted wet meadows in the Sierra Nevada and Cascade Ranges, California, USA”: paper published in Hydrogeology Journal (2009) 17:229–246, by Steven P. Loheide II, Richard S. Deitchman, David J. Cooper, Evan C. Wolf, Christopher T. Hammersmark, Jessica D. Lundquist - Steven P. Loheide; Richard S. Deitchman; David J. Cooper; Evan C. Wolf; Christopher T. Hammersmark; Jessica D. Lundquist (Hydrogeology Journal, 2010)

Comparative genomics based on massive parallel transcriptome sequencing reveals patterns of substitution and selection across 10 bird species - AXEL KÜNSTNER; JOCHEN B. W. WOLF; NICLAS BACKSTRÖM; OSCEOLA WHITNEY; CHRISTOPHER N. BALAKRISHNAN; LAINY DAY; SCOTT V. EDWARDS; DANIEL E. JANES; BARNEY A. SCHLINGER; RICHARD K. WILSON; ERICH D. JARVIS; WESLEY C. WARREN; et al. (Molecular Ecology, 2010)
Next‐generation sequencing technology provides an attractive means to obtain large‐scale sequence data necessary for comparative genomic analysis. To analyse the patterns of mutation rate variation and selection intensity across the avian genome, we performed brain transcriptome sequencing using Roche 454 technology of 10 different non‐model avian species. Contigs from de novo assemblies were aligned to the two available avian reference genomes, chicken and zebra finch. In total, we identified 6499 different genes across all 10 species, with ∼1000 genes found in each full run per species. We found evidence for a higher mutation rate of the Z chromosome than of autosomes (male‐biased mutation) and a negative correlation between the neutral substitution rate ( d S ) and chromosome size. Analyses of the mean d N / d S ratio (ω) of genes across chromosomes supported the Hill–Robertson effect (the effect of selection at linked loci) and point at stochastic problems with ω as an independent measure of selection. Overall, this study demonstrates the usefulness of next‐generation sequencing for obtaining genomic resources for comparative genomic analysis of non‐model organisms.

Replication of long-bone length QTL in the F9-F10 LG,SM advanced intercross - Elizabeth A. Norgard; Joseph P. Jarvis; Charles C. Roseman; Taylor J. Maxwell; Jane P. Kenney-Hunt; Kaitlin E. Samocha; L. Susan Pletscher; Bing Wang; Gloria L. Fawcett; Christopher J. Leatherwood; Jason B. Wolf; James M. Cheverud (Mammalian Genome, 2009)

A framework for understanding the hydroecology of impacted wet meadows in the Sierra Nevada and Cascade Ranges, California, USA - Steven P. Loheide; Richard S. Deitchman; David J. Cooper; Evan C. Wolf; Christopher T. Hammersmark; Jessica D. Lundquist (Hydrogeology Journal, 2009)

Inhibition of interleukin-1β convertase is associated with decrease of neointimal hyperplasia after coronary artery stenting in pigs - Mariann Gyöngyösi; Wolfgang Sperker; Csaba Csonka; Diana Bonderman; Irene Lang; Christoph Strehblow; Christopher Adlbrecht; Maryam Shirazi; Ursula Windberger; Stephen Marlovits; Michael Gottsauner-Wolf; Paul Wexberg; et al. (Molecular and Cellular Biochemistry, 2003)

Pharmacokinetics and Safety of an Anti-Vascular Endothelial Growth Factor Aptamer (NX1838) Following Injection into the Vitreous Humor of Rhesus Monkeys - Daniel W. Drolet; Joyce Nelson; Christopher E. Tucker; Philip M. Zack; Kerry Nixon; Richard Bolin; Mark B. Judkins; James A. Farmer; Julie L. Wolf; Stanley C. Gill; Raymond A. Bendele (Pharmaceutical Research, 2000)